Signaling the Linguistic Sound Among the Ancient and the Modern Speakers of Arabic - Al-Taweel, Emran Ahmed (Journal of Posthumanism, 2025)
The concept of linguistic signaling is one of the modern linguistic concepts around which many linguistic studies have been conducted since De Saussure to the present day. In my research, I have shed light on the signification of the linguistic sound – apart from the linguistic structure - among the ancients and modernists and the examples and opinions they cited, which prove or deny the relationship between the two elements of the linguistic reference of these sounds.I come out with results which entirely prove the signification of the linguistic sound to the Arabic sounds and prove the relationship between its two elements.